Benefits of heart valve clinics for patients: a systematic review - Yuqiang Wang; Siyu He; Yingqiang Guo; Tingqian Cao; Zechao Ran; Xiaoting Li (BMJ Open)
Objective To evaluate the impact of heart valve clinics (HVCs) versus standard of care (SOC) on disease detection, timing of intervention and clinical outcomes in patients with valvular heart disease (VHD).Design A systematic review was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and registered in PROSPERO (CRD42024518787).Data sources PubMed, Embase, Web of Science, Scopus and the Cochrane Library from inception to 1 May 2025.Eligibility criteria Randomised controlled trials or cohort studies comparing patients managed in HVCs with those receiving SOC, and reporting on outcomes such as mortality, cardiac events, time to symptom reporting or symptom severity. Studies were excluded if they lacked detailed HVC protocols, single-arm designs or were published as abstracts only.Data extraction and synthesis Two reviewers independently screened titles, abstracts and full texts, with discrepancies resolved by a senior adjudicator. The Newcastle-Ottawa Scale (NOS) was used to assess the risk of bias. Meta-analysis was not conducted due to heterogeneity among studies.Results Three high-quality prospective cohort studies (N=1082) were included. Two studies reported mortality and cardiac events: one, a before-and-after controlled trial (n=382), recorded 11 deaths in the HVC group; the other reported 4 deaths in the HVC group (n=156) versus 17 deaths in the SOC group (n=156) (p<0.05). Additionally, two studies found that HVCs significantly reduced the interval between symptom onset and reporting (p<0.05), as well as the proportion of patients presenting with severe symptoms (defined as New York Heart Association (NYHA) class or Canadian Cardiovascular Society (CCS) class ≥III).Conclusion HVCs facilitate stratified and precise management of the whole-life cycle of patients with VHD, enhancing early detection and referral, and leading to reduced mortality and major cardiac events compared with SOC.